(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The advanced experience of Pedagogy, as well as the introduction into practice of achievements in education, are important conditions of today. Currently, a huge base of experiments has been formed, which the teacher can use during his career, and he is getting richer every day. But despite this, it is somehow difficult for teachers and future professionals to master these experiences. The position of the educator is especially significant in creating advanced experiences and popularizing them among his professional colleagues. In this article, feedback and feedback will be made about the techniques used in teaching English to students.